Passive voice in the Tawahka language: a typological-functional approach - Ramírez Sorto, David (2025)
This article presents the results of a typological-functional study of the passive voice in the Tawahka language of Honduras. The research explores, analyzes and describes in detail the structural behavior of a type of voice alternation (active-passive), that is frequently found in the natural languages of the world. In this sense, the purpose of the work is to describe the morphosyntactic structure of the passive voice of this Chibcha language belonging to the Misumalpa family. The information above mentioned shows the methodological process that the work follows, which is carried out under a functionalist approach (Givón, 1995; 2001a; 2018; Mithun, 2015), and it is related to the typological studies carried out on the passive voice at a cross-linguistic level (Givón, 2001b; Keenan & Dryer, 2007; Payne, 1997; Pickett & Elson, 1986; Shibatani, 1985, 1988). The results show that Tawahka possesses promotional passive structures, basic and non-basic, morphological, morphological- periphrastic, lexical and periphrastic.